The Use of Webquest For Teaching English Vocabulary in An EFL Young Learners Context - Sadikin, IrmaSavitri (Proceeding of International Conference on Teacher Training and Education, 2016)
In Globalization era, English teaching has been incorporated to the use of internet and virtual reality to buildup language learning which is attracting academic interest. How to create a good English learningenvironment for the Indonesian primary students-whose native language obviously not English- to learnEnglish has become a challenging issue.Â  Web Quest is an inquiry-oriented online learning activity in whichall of the information used by learners nowadays is drawn from the Internet. Online learning languagethrough Web Quest is no longer limited to online communication such as mails, chat, forums, or other onlineactivities for learners to visit occasionally. Some studies also addressed the use of Web Quest as anapplication in online leaning which were integrated in learnersâ study experience and able to promote Englishlearning interest. This study is one of the examples of such issue in which it focuses on the effect of WebQuest-based learning on vocabulary mastery of primary learners. The study took place in Bandung, WestJava. In addition, this was conducted in one of famous English course which is facilitated with the internetand computer as media for learning English language. The researcher took one class as participants of thestudy. They were primary students ranging from 9 to 10 years old that had mostly the same English languagelevel. In addition, this study used pre-experimental design with one group pre-test-post-test design. The resultof the study indicated that using Web Quest was effective in teaching English vocabularies to the primarystudents. This means that there was significant difference of studentsâ achievement in vocabulary masterybefore and after Web Quest treatment.